Biosorption of cadmium, copper and lead by Gracilariopsis bailinae biomass - Janagap, Steve P. (Miagao, Iloilo University of the Philippines in the Visayas, 2007)
Gracilariopsis bailinae biomass was studied for its ability to remove cadmium, copper and lead from separate aqueous solutions of the metal ions.The effect of pH on metal sorption were determined. Sorption equilibrium experiments were conducted at pH 5 and the Langmuir and Freundlich absorption models were fitted to the experimental data. Langmuir model was only applicable to cadmium biosorption with qmax and b values equal to 15.02 mg g-1 and 0.0217 L mg-1, respectively. The qmax and b for copper and lead were insignificant because the biosorption of these two metals poorly adhere to the model. The Freundlich model fitted the data for the three metals well and the order of adsorption capacity was Pb > Cd > Cu while the order of adsorption intensity was Pb > Cu > Cd. FT-IR experiments were conducted to determine the different groups present in the biomass which may be involved in the biosorption. Results showed that amide, sulfates and the polysaccharides present in the biomass an important role in the biosorption.
Special Problem (Master of Chemistry) -- Miagao, Iloilo : University of the Philippines in the Visayas, March 2007.
Keywords: Biomass